Optimizing Treatment of Tumors Using Nanoparticle-Based Medication Delivery Systems - Arun, Jagdish Kumar; Balasubramanian, Jayashree; Mishra, Awakash; Kundra, Danish; Nidhya, M. S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Recent years have seen a substantial increase in interest in using nanoparticles in treating tumors because of their potential to maximize therapeutic results while minimizing adverse effects. Targeted treatment is made possible by the ability of nanoparticles to deliver medications directly to tumor locations. They may specifically attach to tumor cells by functionalizing the nanoparticle's surface with targeting ligands, boosting drug accumulation in the tumor, and minimizing exposure to healthy tissues. Nanoparticles may also make anticancer medications more stable and soluble, facilitating their efficient distribution. Nanoparticle-based therapy, commonly referred to as nanomedicine or nanoparticle-based therapy, is a young area with great promise. When therapeutic drugs are delivered selectively to tumour areas using nanoparticle technology, therapy effectiveness is increased and adverse effects are reduced. Applications for nanoparticle delivery systems in the medical management of different illnesses, particularly cancer therapy, seem promising. Drug distribution is controlled through the characteristics of nanoparticles. The structure of nanoparticles has become the topic of several research in the last few decades, and significant progress has been achieved in this area. To offer conceptual advice regarding subsequent drug delivery of nanoparticles, the article supplied optimization strategies for nanoparticles in three perspectives: improving biocompatibility, targeting effectiveness, and expanding drug loading rate.